2023
DOI: 10.1088/1361-6668/acff26
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniform current distribution in parallel-wound no-insulation high-temperature superconductor coil during ramping and fast discharging operations

Yutong Fu,
Yawei Wang,
Weihang Peng
et al.

Abstract: A parallel-wound no-insulation (PWNI) high-temperature superconductor (HTS) coil is a kind of pancake-shaped no-insulation (NI) coil wound with parallel-stacked HTS tapes, which combines the characteristics of a NI coil and non-twisted stacked-tape cable. It shows a significant advantage in accelerating the ramping response compared with traditional NI HTS coils wound by a single tape, and is a promising alternative for large-scale high-field magnets. The stacked cable approach can lead to current redistributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Multi-tape-bundled REBCO tape windings, as a kind of NI windings, have recently been employed for large-scale REBCO magnets to improve the current characteristics, especially for a short excitation delay [18], [19]. It was reported that the tape-longitudinal currents were unbalanced within bundled tapes during a magnetic field excitation as well as de-excitation [20], [21]. The unbalanced current may deteriorate the thermal stability on the coil, whereas further investigations on the coil stability are needed (e.g., the current distribution during the sudden discharging).…”
Section: Introductionmentioning
confidence: 99%
“…Multi-tape-bundled REBCO tape windings, as a kind of NI windings, have recently been employed for large-scale REBCO magnets to improve the current characteristics, especially for a short excitation delay [18], [19]. It was reported that the tape-longitudinal currents were unbalanced within bundled tapes during a magnetic field excitation as well as de-excitation [20], [21]. The unbalanced current may deteriorate the thermal stability on the coil, whereas further investigations on the coil stability are needed (e.g., the current distribution during the sudden discharging).…”
Section: Introductionmentioning
confidence: 99%